2016
DOI: 10.1161/jaha.115.002984
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Emergency Department Observation Unit Management Algorithm for Atrial Fibrillation

Abstract: BackgroundAtrial fibrillation (AF) is a common, growing, and costly medical condition. We aimed to evaluate the impact of a management algorithm for symptomatic AF that used an emergency department observation unit on hospital admission rates and patient outcomes.Methods and ResultsThis retrospective cohort study compared 563 patients who presented consecutively in the year after implementation of the algorithm, from July 2013 through June 2014 (intervention group), with 627 patients in a historical cohort (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Many institutions have developed outpatient observation units, with 36% of US EDs reporting having observation units in 2007. Multiple studies have demonstrated that use of observation for a limited time in dedicated units can provide equivalent quality care at lower cost than inpatient care for select conditions including toxicology, skin infections, chest pain, syncope, atrial fibrillation, heart failure, and abdominal pain . Unfortunately we were not able to evaluate observation units separated from observations performed in other areas of the hospital and not dependent from the ED.…”
Section: Discussionmentioning
confidence: 96%
“…Many institutions have developed outpatient observation units, with 36% of US EDs reporting having observation units in 2007. Multiple studies have demonstrated that use of observation for a limited time in dedicated units can provide equivalent quality care at lower cost than inpatient care for select conditions including toxicology, skin infections, chest pain, syncope, atrial fibrillation, heart failure, and abdominal pain . Unfortunately we were not able to evaluate observation units separated from observations performed in other areas of the hospital and not dependent from the ED.…”
Section: Discussionmentioning
confidence: 96%
“…Published data support these new paradigms as safe and logistically feasible alternatives to inpatient management of appropriately selected patients with AF 11, 12, 13, 14, 15. The implementation of these strategies has been shown to result in substantial reductions in hospital admission rates and costs 13, 14, 15. However, studies describing these new approaches are relatively small, and the guidelines for management of AF in the ED are not as well validated or widely adopted as other aspects of AF management 26, 27.…”
Section: Discussionmentioning
confidence: 96%
“…This includes early assessment and cardioversion, followed by a brief observation period, and subsequent discharge of stable patients from the ED. Published data support these new paradigms as safe and logistically feasible alternatives to inpatient management of appropriately selected patients with AF 11, 12, 13, 14, 15. The implementation of these strategies has been shown to result in substantial reductions in hospital admission rates and costs 13, 14, 15.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the fact that the pathophysiology of atrial fibrillation (AF) has been investigated extensively for almost a century, the underlying mechanisms remain only partially understood [15]. Conventional theories have focused on electrical and structural remodeling [6].…”
Section: Introductionmentioning
confidence: 99%